Oil-in-water emulsion composition

Through the combination of hydrated clay minerals, hydrophobic powders, water-soluble cellulose derivatives and branched alcohol, the problems of uneven application and insufficient water resistance during use of water-based oil-type cosmetics are solved, achieving uniform application and long-term aesthetic preservation effects, and enhancing the firmness of the skin.

JP2025015159APending Publication Date: 2025-01-30NARISU COSMETIC CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023118358
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

The existing water-based oil-type cosmetic formulas are prone to uneven application due to moisture evaporation during use, which affects the beauty and lacks water resistance, and is difficult to maintain uniformity for a long time and firmness of the skin.

Method used

A combination of hydrated clay minerals, hydrophobic powders, water-soluble cellulose derivatives and branched alcohol components in a specific proportion is used to form a stable emulsification system, avoiding the use of traditional surfactants.

Benefits of technology

It realizes uniform application of cosmetics on the skin, improves water resistance and long-term aesthetic retention ability, while enhancing the firmness of the skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015159000001
    Figure 2025015159000001
  • Figure 2025015159000002
    Figure 2025015159000002
  • Figure 2025015159000003
    Figure 2025015159000003
Patent Text Reader

Abstract

To provide an oil-in-water emulsion composition that offers superior long-term cosmetic performance, prevents color irregularities during manufacturing, ensures superior uniform spreadability of a coating film during skin application, enhances skin firmness after application, and delivers superior emulsion stability.SOLUTION: An oil-in-water emulsion composition contains following components (A)-(D). Component (A): 0.1 mass%-3.0 mass% of a water-swellable clay mineral, component (B): a hydrophobic powder, component (C): a water-soluble cellulose derivative, and component (D): 1.0 mass%-5.0 mass% of a branched higher alcohol.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oil-in-water emulsion composition, and more specifically, to an oil-in-water emulsion composition which is free of color unevenness during production, exhibits excellent uniform spreadability of a coating film when applied to the skin, has excellent cosmetic durability over time, provides an excellent feeling of firmness after application, and also exhibits excellent emulsion stability. [Background technology]

[0002] Foundation, a type of base makeup product, covers imperfections such as blemishes and freckles and makes the skin look beautiful, and is broadly divided into three types: powder foundation, emulsion foundation, and oil-based foundation. Consumers purchase foundations taking into consideration their skin type, age, purpose, and the season of use. Of the three types, emulsion foundations are highly moisturizing and emollient, making them easy to obtain skin care effects, and are therefore always in high demand among consumers. There are two types of emulsion foundations: water-in-oil type, in which the continuous phase is oil, and oil-in-water type, in which the continuous phase is water. Water-in-oil type foundations have excellent water resistance and tend to have good makeup wear because the continuous phase is oil, but they often contain volatile oily ingredients, which has the disadvantage of making the foundation feel dry. In addition, if no volatile oily ingredients are included, the foundation feels oily and is not very popular for use in the summer. On the other hand, oil-in-water type foundations contain a lot of water, so they are less likely to feel sticky, have a fresh and comfortable feel, and are also prone to moisturizing. However, since the continuous phase of oil-in-water type foundations is water, they are easily absorbed by sweat and tears, which causes makeup to break down over time, and they have the disadvantage of not having sufficient makeup durability. In order to solve this problem, it has been disclosed that a hydrophobically treated powder is blended with an oil-soluble resin (Patent Document 1). However, in order to stably emulsify and homogenize the oil phase containing a highly hydrophobic oil-soluble resin, it was necessary to blend a highly hydrophilic surfactant. However, when highly hydrophilic surfactants are added, water resistance decreases and the cosmetic film easily peels off due to re-emulsification with sweat and tears, resulting in problems such as insufficient makeup durability.

[0003] Also, an oil-in-water emulsion foundation that contains an alkyl-modified carboxyvinyl polymer, which is a water-soluble thickener, a hydrophobized powder, and a silicone resin, and does not substantially contain a surfactant, has been disclosed (Patent Document 2). This composition contains a hydrophobized powder in the oil of the oil-in-water emulsion, and therefore the powder maintains a hydrophobized state compared to conventional foundations, and is compatible with the silicone resin that covers the skin, so that it has the advantage of being highly water-resistant when applied and long-lasting. However, since the coloring agent used in foundations is based on hydrophilic pigments such as iron oxide and titanium oxide, it is difficult to uniformly disperse the pigment in the oil and maintain that state for a long period of time unless a surfactant with good pigment dispersibility is added. If the pigment dispersion effect is not sufficiently obtained, the pigment will aggregate. At this time, if the pigment aggregates severely and becomes visible from the outside, a defective appearance called color unevenness will occur. If color unevenness occurs during production, even if the color unevenness is made less noticeable by stirring afterwards, color unevenness is likely to occur again over time during storage, filling, and after filling the container. Furthermore, pigments aggregate and become non-uniform, which causes a discrepancy between the appearance color of the formulation and the color applied to the skin, making it difficult for consumers to choose a formulation that matches their own skin tone. Therefore, there was a need to develop a technology that improves water resistance without causing pigment aggregation and uneven coloring.

[0004] Furthermore, in an emulsion system using a polymeric emulsifier such as an alkyl-modified carboxyvinyl polymer, the lipophilic group portion is adsorbed to the dispersed phase, and the hydrophilic group portion is swollen by the water of the continuous phase to form a hydrated gel phase, thereby preventing the disperse phase from coalescing and stabilizing the system, so that a stable emulsion system can be formed without the addition of a so-called surfactant. However, since the external phase of an oil-in-water emulsion is a water phase, immediately after application, the skin is in a lipophobic state in which a thin aqueous phase spreads, and the oily dispersed phase that does not contain a surfactant does not blend in. After that, the dispersed phase is fixed in sequence from the area where the water has evaporated, making it difficult to obtain a uniform application state. At this time, if the oil-in-water emulsion is a foundation, only the applied area is colored, so the mottled state is easy to see. Furthermore, if the polymeric emulsifier forms a hydrated gel, the hydrated gel phase does not blend in well on the skin, making the mottled state more noticeable. In order to spread evenly without becoming mottled, it is desirable for the composition to have high spreadability, but this is in a trade-off relationship with viscosity and stability, and it has been difficult to achieve both.

[0005] Patent Document 3 discloses that the oil-in-water makeup cosmetic, which contains water-swellable clay minerals, fatty acid soap, silicone oil, and batyl alcohol (glycerin monostearyl ether), is an emulsified composition using only a small amount of fatty acid soap, which is a hydrophilic surfactant, as an emulsifier, and is excellent in stability, safe for the skin, has a good feel when used, and has good cosmetic durability (water resistance). However, since a hydrophilic pigment is used without being hydrophobized, there is a high possibility of pigment aggregation in the oil agent, and there is concern that the appearance color of the formulation and the color applied to the skin may differ or become uneven.

[0006] In addition, the skin of the human face, etc., loses firmness and elasticity due to external stimuli such as aging, dryness, and ultraviolet rays, and sags and wrinkles occur, making it difficult to make the face look youthful. Conventionally, in particular in preparations such as foundations that are used during the day and washed off with a cleansing agent at night, a method has been known that uses a visual lift-up effect to give a youthful facial impression in order to make the face look youthful (Patent Document 4). However, in conventional methods, although they have a visual effect on third parties, they do not have an effect of actually making the user feel firm, so the actual user cannot tell whether the skin looks firm and youthful, which makes them feel uneasy.

[0007] Generally, linear higher alcohols are often blended into oil-in-water emulsion compositions. It is known that when linear higher alcohols are blended into oil-in-water compositions, they form a strong interfacial membrane of an association (α-gel) consisting of a lamellar bilayer membrane in the presence of a surfactant and water, improving the stability of the composition (Patent Document 5, Patent Document 6). On the other hand, branched higher alcohols are difficult to form α-gel, and in the cosmetic field, they are mostly used as emulsifying aids, to improve the feel of use by improving the spreadability due to their liquid form, and to have high pigment dispersion ability due to their side chains, and since these are easily replaced with other ingredients already blended, there are few examples of branched higher alcohols being actively used in oil-in-water compositions (Patent Document 7).

[0008] For the above reasons, there has been a demand for an oil-in-water emulsion composition which is free of color unevenness during production, has excellent uniform spreadability when applied to the skin, has excellent cosmetic durability over time, and further has an excellent firmness after application and excellent emulsion stability. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 1-261316 [Patent Document 2] Japanese Patent Application Publication No. 11-043417 [Patent Document 3] JP 2018-016587 A [Patent Document 4] JP 2005-097218 A [Patent Document 5] JP 2010-006716 A [Patent Document 6] JP 2015-182994 A [Patent Document 7] JP 2010-053150 A Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made in consideration of the above-mentioned conventional techniques, and an object of the present invention is to provide an oil-in-water emulsion composition which is free of color unevenness during production, has excellent uniform spreadability when applied to the skin, has excellent cosmetic durability over time, provides an excellent feeling of firmness after application, and has excellent emulsion stability. [Means for solving the problem]

[0011] Means of Solving the Problems The present inventors conducted intensive research to achieve the above-mentioned object and discovered that an oil-in-water emulsion composition containing specific components can solve all of the above-mentioned problems, thereby completing the present invention.

[0012] That is, the present invention provides: The cosmetic composition comprises the following components (A) to (D). Component (A): 0.1% to 3.0% by mass of water-swellable clay minerals Component (B): Hydrophobic powder Component (C): Water-soluble cellulose derivative Component (D): 1.0% to 5.0% by mass of branched higher alcohol Effect of the Invention

[0013] According to the present invention, it is possible to provide an oil-in-water emulsion composition which is free from color unevenness during production, has excellent uniform spreadability of a coating film when applied to the skin, has excellent cosmetic durability over time, provides an excellent firmness after application, and has excellent emulsion stability. BEST MODE FOR CARRYING OUT THEINVENTION

[0014] The present invention will be described in more detail below. Unless otherwise noted, the amount of each component expressed as "%" below means % by mass.

[0015] The water-swellable clay mineral (A) used in the present invention is known as a layered inorganic additive. It is not particularly limited, but specifically includes bentonite (including natural or synthetic bentonite), montmorillonite (including natural or synthetic montmorillonite), beidellite, nontronite, saponite, sauconite, hectorite (including natural or synthetic hectorite), stevensite and other smectite clay minerals, synthetic silicates, vermiculite, swelling synthetic fluorine mica (Na-type, Li-type synthetic mica), swelling mica, etc., and may be either natural or synthetic. Commercially available water-swellable clay minerals, such as Kunipia, Sumecton (both from Kunimine Industries), Veegum (Vanderbilt), Laponite (BYK Japan), and fluorotetrasilicic mica (Topy Industries), can be used.

[0016] The amount of the water-swellable clay mineral (A) in the present invention is not particularly limited as long as the effects of the present invention can be obtained, but it is usually used in the range of 0.1 to 3.0 mass % and preferably 0.4 to 1.0 mass % based on the total amount of the cosmetic composition. In this range, the effect of suppressing color unevenness is very excellent, and in the range of 3.0 mass % or less, the cosmetic finish is good.

[0017] The water-swellable clay mineral of component (A) may be used alone or in combination.

[0018] The hydrophobic powder, component (B) used in the present invention, refers to two types: a powder obtained by subjecting a hydrophilic base powder to a hydrophobic surface treatment, and a powder in which the base powder itself is hydrophobic.

[0019] The hydrophilic powder that is the base of component (B) is not particularly limited by its shape (e.g., plate-like, spindle-like, needle-like, etc.), its particle size (e.g., mist-like, fine particles, pigment-grade, etc.), its particle structure (e.g., porous, non-porous, etc.), and examples thereof include inorganic powders, glittering powders, colored pigments, and composite powders.

[0020] Among the hydrophilic powders that serve as the base for component (B), examples of inorganic powders include carbon black, magnesium carbonate, calcium carbonate, chromium oxide, chromium hydroxide, aluminum silicate, magnesium silicate, aluminum magnesium silicate, titanium oxide, zinc oxide, aluminum oxide, cerium oxide, magnesium oxide, zirconium oxide, iron oxide, mica, synthetic mica, sericite, synthetic sericite, talc, kaolin, silicon carbide, barium sulfate, boron nitride, and silica.

[0021] Examples of luster powders include bismuth oxychloride, titanium mica, iron oxide treated mica, titanium mica treated with iron oxide, titanium mica treated with organic pigments, silicon dioxide / titanium oxide coated mica, titanium oxide coated glass powder, iron oxide / titanium oxide coated glass powder, and aluminum powder.

[0022] Examples of colored pigments include inorganic red pigments such as red iron oxide (red iron oxide), iron hydroxide, iron titanate, etc., inorganic brown pigments such as gamma-iron oxide, inorganic yellow pigments such as yellow iron oxide, ocher, etc., inorganic black pigments such as black iron oxide, carbon black, etc., inorganic purple pigments such as manganese violet, cobalt violet, etc., inorganic green pigments such as chromium hydroxide, chromium oxide, cobalt oxide, cobalt titanate, etc., inorganic blue pigments such as iron blue and ultramarine, lakes made from tar-based dyes using aluminum or the like, lakes made from natural dyes, and synthetic resin powders made by combining these powders. Examples of tar dyes include Red No. 3, Red No. 104, Red No. 106, Red No. 201, Red No. 202, Red No. 204, Red No. 205, Red No. 220, Red No. 226, Red No. 227, Red No. 228, Red No. 230, Red No. 401, Red No. 505, Yellow No. 4, Yellow No. 5, Yellow No. 202, Yellow No. 203, Yellow No. 204, Yellow No. 401, Blue No. 1, Blue No. 2, Blue No. 201, Blue No. 404, Green No. 3, Green No. 201, Green No. 204, Green No. 205, Orange No. 201, Orange No. 203, Orange No. 204, Orange No. 206, and Orange No. 207.

[0023] Examples of composite powders include titanium oxide coated mica, iron oxide coated mica, iron oxide coated titanium mica, zinc oxide coated titanium mica, barium sulfate coated titanium mica, organic pigment treated titanium mica, silicon dioxide / titanium oxide coated mica, titanium oxide coated glass powder, iron oxide / titanium oxide coated glass powder, titanium oxide containing silicon dioxide, zinc oxide containing silicon dioxide, barium sulfate coated titanium mica, etc.

[0024] Examples of hydrophobic surface treatments for the component (B) hydrophobic powder used in the present invention include silicone treatment, silylation treatment, alkyl titanate treatment, metal soap treatment, oil treatment, fluorine compound treatment, phospholipid treatment, etc. There are no particular limitations, and treatments that are normally used in cosmetics can be used.

[0025] Examples of the silicone in the silicone treatment include chain silicones such as low polymerization degree dimethylpolysiloxane, high polymerization degree dimethylpolysiloxane, methylhydrogenpolysiloxane, and methylphenylpolysiloxane; modified silicones such as alkyl-modified silicone and alkoxy-modified silicone; silicone resins such as trimethylsiloxysilicate and acrylate silicone; silicone rubbers; and partially or fully crosslinked organopolysiloxanes.

[0026] The silylation treatment uses a silylating agent, and an example of this is trialkoxyalkylsilane treatment. The trialkoxyalkylsilane in the trialkoxyalkylsilane treatment is a compound in which three alkoxy groups and one alkyl group are bonded to a silicon atom, and the alkoxy group reacts with hydroxyl groups or the like on the powder surface to chemically coat the powder surface. In the trialkoxyalkylsilane, the alkoxy group is preferably a methoxy, ethoxy, propoxy, or the like having 1 to 3 carbon atoms. In addition, in the trialkoxyalkylsilane, the alkyl group is preferably a hexyl group, octyl group, decyl group, octadecyl group, or the like having 6 to 18 carbon atoms. Examples of such trialkoxyalkylsilanes include trimethoxyhexylsilane, trimethoxyoctylsilane, trimethoxydecylsilane, trimethoxyoctadecylsilane, triethoxyhexylsilane, triethoxyoctylsilane (triethoxycaprylylsilane), triethoxydecylsilane, triethoxyoctadecylsilane, etc. Other examples of silylating agents used in the silylation treatment include triethylchlorosilane, trimethylchlorosilane, diethyldichlorosilane, dimethyldichlorosilane, acetoxytrimethylsilane, acetoxysilane, diacetoxydimethylsilane, etc.

[0027] Examples of the alkyl titanate in the alkyl titanate treatment include long-chain carboxylic acid type, pyrophosphate type, phosphorous acid type, amino acid type, etc. Specifically, examples of the long-chain carboxylic acid type alkyl titanate include isopropyl triisostearoyl titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, diisostearoyl ethylene titanate, etc., and examples of the pyrophosphate type alkyl titanate include tetraisopropyl bis(dioctyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, etc. Examples of phosphorous-type alkyl titanates include isopropyl tri(dioctylpyrophosphate) titanate, bis(dioctylpyrophosphate)oxyacetate titanate, and bis(dioctylpyrophosphate)ethylene titanate. Examples of amino acid-type alkyl titanates include isopropyl tri(N-amidoethyl, aminoethyl) titanate.

[0028] Examples of the metal soap used in the metal soap treatment include zinc laurate and zinc stearate.

[0029] Examples of the oil used in the oil treatment include polyisobutylene, wax, higher fatty acids, and higher alcohols.

[0030] Examples of fluorine compounds used in the fluorine compound treatment include perfluoroalkyl phosphoric acid and its salts, perfluoropolyether, fluoroalkoxysilane, perfluoroalkylalkoxysilane (e.g., perfluorooctyltriethoxysilane), perfluoropolyether alkyl phosphoric acid and its salts, and perfluoroalkylsilane.

[0031] The phospholipids in the phospholipid treatment include phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, phosphatidylglycerol, phosphatidylinositol, sphingophospholipids, and the like, as well as their analogs or compositions containing them, i.e., soybean lecithin, egg yolk lecithin, or hydrogenated products thereof.

[0032] Powders of component (B) that are hydrophobic in themselves are not particularly limited by shape (plate, spindle, needle, etc.), particle size (aerosol, fine particles, pigment-grade, etc.), particle structure (porous, non-porous, etc.), and examples include organic powders, polyethylene terephthalate-aluminum-epoxy laminated powder, polyethylene terephthalate-polymethyl methacrylate laminated powder, etc. There is no problem if the powders that are hydrophobic in themselves are further subjected to hydrophobic surface treatment, but if they are subjected to hydrophilic surface treatment, they are omitted from component (B).

[0033] Examples of organic powders include metal soap powders such as zinc laurate, zinc myristate, zinc stearate, magnesium laurate, magnesium myristate, and magnesium stearate, N-acyl lysine, nylon, polymethylsilsesquioxane, crosslinked organopolysiloxane polymers, polystyrene, polyurethane, polyethylene, polypropylene, polymethacrylic acid esters such as polymethyl methacrylate, complexes of polymethyl methacrylate and polyisoprene, polyacrylic acid esters, acrylonitrile-methacrylic acid copolymer powder, and polytetrafluoroethylene. Examples of crosslinked organopolysiloxane polymers include partially crosslinked methylpolysiloxanes such as (dimethicone / vinyl dimethicone) crosspolymer, partially crosslinked methylphenylpolysiloxanes such as (dimethicone / phenyl dimethicone) crosspolymer, partially crosslinked polyether modified silicones such as dimethicone copolyol crosspolymer, partially crosslinked alkyl modified silicones, partially crosslinked alkyl / polyether modified silicones such as (lauryl dimethicone / PEG) crosspolymer, and the like. For example, the INCI names include (dimethicone / vinyl dimethicone) crosspolymer, (dimethicone / phenyl vinyl dimethicone) crosspolymer, (dimethicone / vinyl dimethicone / methicone) crosspolymer, (dimethicone / lauryl dimethicone) crosspolymer, (diphenyl dimethicone / vinyl diphenyl dimethicone / silsesquioxane) crosspolymer, and (vinyl dimethicone / methicone silsesquioxane) crosspolymer. The crosslinked organopolysiloxane polymer may be blended in the form of a silicone gel consisting of a crosslinked organopolysiloxane polymer and a solvent. Commercially available silicone gels can be used, such as KSG-18A, KSG-16, KSG-15AP (all manufactured by Shin-Etsu Silicone Co., Ltd.), and Elastomer Blend DC9045 (manufactured by Dow Corning Toray Co., Ltd.).

[0034] The amount of the hydrophobic powder (B) in the present invention is not particularly limited as long as the effects of the present invention can be obtained, but it is usually used in the range of 5.0 to 50.0% by mass, preferably 10.0 to 35.0% by mass, based on the total amount of the cosmetic composition. In this range, the cosmetic durability over time is very excellent, and at 50.0% by mass or less, the emulsion stability is good.

[0035] The hydrophobic powder of component (B) may be used alone or in combination of two or more kinds.

[0036] The water-soluble cellulose derivative (C) used in the present invention is a derivative in which a part of the hydroxyl group of crystalline cellulose, which is a linear polymer, is replaced with a hydrophobic group to improve the solubility in water. Examples of the hydrophobic group include an acetyl group, an alkyl group, a phenyl group, an epoxy group, and a maleic functional group. The hydrophobic group to be substituted may be one type or a combination of two or more types. The component (C) used in the present invention is not particularly limited, but preferred components include hydroxypropyl methylcellulose stearoxy ether (product names: Sangelose 60M, Sangelose 60L, Sangelose 90M, Sangelose 90L, all manufactured by Daido Chemical Industry Co., Ltd.), ethyl hydroxyethyl cellulose (BERMOCOLL EHM, manufactured by Akzo Nobel), hydroxypropyl methylcellulose (BENECEL K100M, manufactured by Ashland Japan), stearoxy PG hydroxyethyl cellulose sodium sulfonate (Poise 310, manufactured by Kao Corporation), cellulose gum, and the like, and among these, nonionic water-soluble cellulose is preferred.

[0037] The amount of the water-soluble cellulose derivative (C) in the present invention is not particularly limited as long as the effects of the present invention are obtained, but it is usually used in the range of 0.005 to 0.5% by mass, preferably 0.01 to 0.1% by mass, based on the total amount of the cosmetic composition. Within this range, the skin after application is very firm, and the cosmetic finish is particularly good at 0.1% by mass or less.

[0038] The water-soluble cellulose derivatives as component (C) may be used singly or in combination of two or more.

[0039] The branched higher alcohol (Component (D)) used in the present invention has a branched carbon chain in the molecule. Component (D) is not particularly limited, but examples thereof include isostearyl alcohol, octyldodecanol, hexyldecanol, and decyltetradecanol.

[0040] The blending amount of the component (D) branched higher alcohol in the present invention is not particularly limited as long as the effects of the present invention can be obtained. Generally, the blending amount is 1.0 to 5.0% by mass based on the total amount of the cosmetic composition. The amount used is preferably within the range of 1.5 to 4.0% by mass, in which case the coating film has excellent uniform spreadability upon application, and at 5.0% by mass or less the emulsion stability is good.

[0041] In the present invention, the component (E) may contain a hydrophilic surfactant. The component (E) has a high HLB value and is at least one selected from nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants. If the component (C) of the present invention contains a component that satisfies the conditions of component (E), the component is excluded from component (E). Among the components (E), it is most preferable to use a nonionic surfactant, and it is preferable to use an anionic surfactant. Specifically, examples of nonionic surfactants include glycerin fatty acid esters, polyglycerin fatty acid esters, propylene glycol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, or alkylene glycol adducts of these fatty acid esters; polyalkylene glycol fatty acid esters, polyoxyalkylene alkyl ethers, glycerin alkyl ethers, polyoxyethylene hydrogenated castor oil, etc. Examples of anionic surfactants include diacylglutamic acid lysine salts; fatty acid salts derived from fatty acids such as sodium dilauroyl glutamic acid lysine, sodium dimyristoyl glutamic acid lysine, sodium distearoyl glutamic acid lysine, and sodium laurate; monosodium N-lauroyl glutamate, long-chain N-acyl glutamates; sodium N-stearoyl-L-glutamate, arginine N-stearoyl-L-glutamate, sodium N-stearoyl glutamate, sodium N-myristoyl-L-glutamate, alkyl phosphates; sodium lauryl phosphate, and potassium cetyl phosphate. The component (E) preferably has an HLB value of 12 or more, and particularly preferred components include ceteth-20 (HLB=17) and polyoxyethylene hydrogenated castor oil (HLB=13).

[0042] In the present invention, when the component (E) hydrophilic surfactant is contained, its blending amount is preferably 1.0 mass % or less based on the total amount of the cosmetic composition. Hydrophilic surfactants are originally used as a main component of cleansers, and reduce the water resistance of cosmetics and impair makeup wear, but the combination of the present invention has been found to have the effect of improving makeup wear.

[0043] The hydrophilic surfactants as component (E) may be used singly or in combination of two or more.

[0044] HLB is a value that indicates the hydrophilic-hydrophobic balance usually used in the field of surfactants, and a commonly used calculation formula, such as the Kawakami formula, can be used. In the present invention, the following Kawakami formula is adopted.

number

[0045] In addition to the above essential components, the composition of the present invention can also contain components generally used in cosmetics, etc., as necessary. For example, pearlescent agents, moisturizing agents, thickeners, water-soluble polymers other than component (C), fragrances, bactericides, preservatives, antioxidants, pH adjusters, chelating agents, UV absorbers, anti-inflammatory agents, antioxidants, cooling agents, herbal extracts, vitamin additives, etc. can be added as appropriate. The blending ratio of these components when they are added can be appropriately selected depending on their types and purposes, and one type may be used alone, or two or more types may be used in appropriate combination. EXAMPLES

[0046] The present invention will be further described below with reference to examples, but the present invention is not limited to these examples in any way. (Manufacturing method) (a) Heat the water-soluble ingredients in Table 1 to 90°C, dissolve and homogenize. (b) Heat the non-water-soluble components and the oil-soluble components in Table 1 to 90°C, dissolve and homogenize. The (a) was added to the (b) and emulsified by stirring using a homomixer, and then cooled to 35° C. to obtain an oil-in-water emulsion composition.

[0047] <Evaluation item 1> <Method for evaluating color unevenness during manufacturing> <Evaluation method> The color unevenness was evaluated at the end of cooling in the above-mentioned production method. The same formulation was manufactured three times, and ten expert judges visually evaluated the products and rated them on a four-level scale according to the following criteria. <Evaluation criteria> ◎: Good - 9 or more engineers answered that there was no color unevenness 〇: Fairly good 7 to 8 technicians answered that there was no uneven coloring △: Somewhat poor 5 to 6 technicians answered that there was no color unevenness ×: Poor - Four or fewer technicians answered that there was no color unevenness.

[0048] <Evaluation item 2> <Uniform spreadability of coating film when applied> <Evaluation method> The uniform spreadability of the coating film when applied was evaluated using a sensory characteristic evaluation test. After washing their faces, 10 expert judges applied a pearl-sized amount of each sample to their entire faces after applying a specific face lotion and milky lotion. The uniform spreadability of the coating film when applied to each sample was evaluated according to the following criteria. <Evaluation criteria> ◎: Good - 9 or more judges answered that the coating has uniform spreadability. 〇: Fairly good Seven to eight judges answered that the coating has uniform spreadability. △: Somewhat poor. Five to six judges answered that the coating has uniform spreadability. ×: Poor - Four or fewer judges answered that the coating film had uniform spreadability.

[0049] <Evaluation item 3> <Cosmetic durability over time> <Evaluation method> The cosmetic durability over time was evaluated using a sensory property evaluation test. After washing their faces, 10 expert judges applied a pearl-sized amount of each sample to the entire face after applying a specific face lotion and milky lotion. Each sample was scored according to the following evaluation criteria to see if the cosmetic film remained on the skin after 6 hours, and the average score was determined as follows: over 4.0 = ◎, over 3.0 and 4.0 = ◯, over 2.0 and 3.0 = △, and 2.0 or less = ×. <Evaluation criteria> 5: The cosmetic film is well maintained. 4: The cosmetic film is maintained. 3: I can't say either way. 2: The cosmetic film is not maintained very well. 1: The cosmetic film is not maintained at all.

[0050] <Evaluation item 4> <Water resistance> <Evaluation method> Regarding water resistance, 10 expert judges applied the cosmetics to the inside of the forearm, and six hours later, they ran running water over the cosmetic film for 30 seconds. They then compared the cosmetic film before and after the water was removed and assigned a score according to the following evaluation criteria to determine whether the cosmetic film remained on the skin. The average score was then assigned as ◎ for over 4.0, ◯ for over 3.0 and 4.0, △ for over 2.0 and 3.0, and × for 2.0 or less. <Evaluation criteria> 5: The cosmetic film is well maintained. 4: The cosmetic film is maintained. 3: I can't say either way. 2: The cosmetic film is not maintained very well. 1: The cosmetic film is not maintained at all.

[0051] <Evaluation item 5> <Skin firmness after application> <Evaluation method> The firmness of the skin after application was evaluated using a sensory property evaluation test. Ten expert judges washed their faces, then applied a specific face lotion and milky lotion to the face, and then applied a pearl-sized amount of each sample to the entire face. The firmness of the skin after application of each sample was scored according to the following evaluation criteria, and the average score was determined as follows: over 4.0 = ◎, over 3.0 to 4.0 = ○, over 2.0 to 3.0 = △, and 2.0 or less = ×. <Evaluation criteria> 5: The firmness is excellent. 4: You can feel the firmness. 3: I can't say either way. 2: The firmness is slightly lacking and is undesirable. 1: No firmness at all.

[0052] <Evaluation item 6> <Emulsification stability> <Evaluation method> The emulsion composition was filled into a transparent container and stored at 40°C for 4 weeks. The composition was then scooped out with a spatula or the like, and the internal and surface conditions of the composition were visually inspected by a specialist assessor, who then evaluated the emulsion stability according to the following criteria. ⊚: Good: No particular change in the emulsion composition. ◯: Fairly good: Slight unevenness can be observed in the appearance of the emulsion composition, but there is no oil bleeding on the surface of the composition, and there is no problem in terms of product quality. ×: Poor: Oil bleeding was observed on the surface of the composition, and there was a problem with the product quality.

[0053] [Table 1] *1: Trimethoxyhexylsilane treatment

[0054] [Table 2]

[0055] [Table 3]

[0056] As can be seen from the table, Examples 1 to 22 of the present invention obtained good results in all evaluation items compared to the comparative examples. On the other hand, Comparative Example 1, in which the amount of component (A) was small, did not have the effect of suppressing color unevenness, and satisfactory quality could not be obtained. In Comparative Example 2, in which the amount of component (A) was exceeded, the effect of suppressing color unevenness was confirmed, but the uniform spreadability of the coating film upon application was not satisfactory. Comparative Example 3, in which the amount of component (D) was small, did not have the uniform spreadability of the coating film upon application, and the finish was poor. Comparative Example 4, in which the amount of component (D) was exceeded, had poor emulsion stability. Comparative Example 5, in which a non-hydrophobic powder was added instead of component (B), had poor makeup durability over time. In Comparative Examples 6 to 8, in which a water-soluble thickener not containing cellulose was added instead of component (C), no firmness was felt. Comparative Examples 9 to 11, in which an unbranched higher alcohol was used instead of component (D), and Comparative Example 12, in which component (D) was not used, showed poor uniform spreadability of the coating film upon application, and the finish (aesthetics) was unsatisfactory.

[0057] Compositions having the following formulations were prepared in a conventional manner. It was confirmed that the effects of the present invention were achieved in all of the formulations.

[0058] (1) <Emulsion Foundation> Ingredients Amount (%) Cetanol 1.5 Glyceryl myristate 0.65 Seteth -20 0.5 PEG-50 hydrogenated castor oil 0.2 Liquid Paraffin 5.5 Triethylhexanoin 2.0 Octyldodecanol 1.2 Hexyldecanol 0.3 Dimer dilinoleate dimer dilinoleyl 2.0 Isododecane 3.0 Dimethicone 0.5 Diphenyl Dimethicone 0.5 Polyglyceryl-2 Isostearate 1.1 Cholesterol 1.0 Tocopherol 0.2 (Dimethicone / vinyl dimethicone) crosspolymer 0.5 water residue 1,3-Butylene glycol 8.0 Hydrogenated lecithin 0.3 Glycerin 4.0 Nicotinamide 0.1 Bentonite 0.9 Montmorillonite 0.1 (Acrylates / alkyl acrylate (C10-30)) crosspolymer 0.1 Hydroxypropyl methylcellulose stearoxy ether 0.01 (Acryloyldimethyltaurate ammonium / VP) copolymer 0.045 Sodium hyaluronate 0.01 Ethylhexylglycerin 0.2 Phenoxyethanol 0.3 Ethyl Cocoyl Arginate PCA 0.1 Alumina 0.15 (Vinyl Dimethicone / Methicone Silsesquioxane) Crosspolymer 3.0 Hydrophobically treated titanium dioxide (dimethicone treatment) 25.0 Hydrophobic titanium oxide (treated with trimethoxyhexylsilane) 5.0 Hydrophobically treated iron oxide (treated with dimethicone) 3.6 Hydrophobized iron oxide (treated with isopropyl triisostearoyl titanate) 1.4 Talc 2.6 Total 100

[0059] (2) <Makeup base> Ingredients Amount (%) Hydrogenated rapeseed alcohol 1.5 Glyceryl myristate 0.65 Seteth -20 0.1 PEG-50 hydrogenated castor oil 0.2 Hydrogenated polyisobutene 5.5 Triethylhexanoin 2.0 Octyldodecanol 3.0 Hexyldecanol 1.0 Dimer dilinoleate dimer dilinoleyl 2.0 Dimethicone 0.5 Diphenyl Dimethicone 0.5 Polyglyceryl-2 Isostearate 1.1 Cholesterol 1.0 Tocopherol 0.2 (Dimethicone / vinyl dimethicone) crosspolymer 0.5 water residue 1,3-Butylene glycol 8.0 Glycerin 5.0 Bentonite 2.2 Montmorillonite 0.5 Silicate (Na / Mg) 0.3 Xanthan gum 0.1 Hydroxypropyl methylcellulose stearoxy ether 0.08 Hydroxypropyl methylcellulose 0.02 (Acryloyldimethyltaurate ammonium / VP) copolymer 0.045 Sodium Dilauramidoglutamide Lysine 0.3 Sodium hyaluronate 0.01 Ethylhexylglycerin 0.2 Phenoxyethanol 0.3 Iodide propynyl butylcarbamate 0.003 Alumina 0.15 Hydrophobically treated titanium dioxide (dimethicone treatment) 7.5 Hydrophobically treated iron oxide (treated with dimethicone) 2.5 Talc 3.6 Total 100

[0060] (3) <Sunscreen cosmetics> Ingredients Amount (%) Seteth -1 1.5 Glyceryl myristate 0.65 Seteth -20 0.5 PEG-50 hydrogenated castor oil 0.2 (VP / Eicosene) Copolymer 0.5 Hydrogenated polyisobutene 5.5 Triethylhexanoin 1.0 Octyldodecanol 3.0 Hexyldecanol 1.0 Dimer dilinoleate dimer dilinoleyl 2.0 Dimethicone 0.5 Diphenyl Dimethicone 0.5 Polyglyceryl-2 Isostearate 1.1 Cholesterol 1.0 Tocopherol 0.2 (Dimethicone / vinyl dimethicone) crosspolymer 0.5 water residue 1,3-Butylene glycol 8.0 Glycerin 5.0 Bentonite 2.5 Montmorillonite 0.5 Xanthan gum 0.1 (PEG-240 / Decyltetradeceth-20 / HDI) copolymer 0.05 Hydroxypropyl methylcellulose stearoxy ether 0.08 Stearoxy PG Hydroxyethylcellulose Sodium Sulfonate 0.02 (Acryloyldimethyltaurate ammonium / VP) copolymer 0.045 Sodium hyaluronate 0.01 Retinol Palmitate 0.05 Ethylhexylglycerin 0.2 Phenoxyethanol 0.3 Alumina 0.15 Hydrophobically treated titanium dioxide (dimethicone treatment) 7.5 Hydrophobically treated iron oxide (treated with dimethicone) 2.5 Talc 3.6 Total 100

Claims

1. An oil-in-water emulsion composition comprising the following components (A) to (D): Component (A): 0.1% by mass to 3.0% by mass of water-swellable clay mineral Component (B): Hydrophobic powder Component (C): Water-soluble cellulose derivative Component (D): 1.0% by mass to 5.0% by mass of a branched higher alcohol

2. 5.0% by mass to 50.0% by mass of component (B); The oil-in-water emulsion composition according to claim 1, comprising 0.005% by mass to 0.5% by mass of component (C).

3. 3. The oil-in-water emulsion composition according to claim 1, wherein the component (C) is a nonionic water-soluble cellulose derivative.

4. The oil-in-water emulsion composition according to claim 3 , further comprising a component (E) hydrophilic surfactant, the component (E) being present in an amount of 1.0% by mass or less in the composition.

Citation Information

Patent Citations

  • Oil-in-water type emulsified cosmetic

    JP1989261316A

  • Oil-in-water type emulsion cosmetic

    JP1999043417A

  • Foundation

    JP2005097218A

  • alpha GEL-CONTAINING COMPOSITION

    JP2010006716A

  • Oil-in-water type emulsified cosmetic

    JP2010053150A